Solution Algorithms for Single-Machine Group Scheduling with Learning Effect and Convex Resource Allocation. (3rd March 2021) - Wang, Wanlei; Wang, Jian-Jun; Wang, Ji-Bo
Abstract : This paper deals with a single-machine resource allocation scheduling problem with learning effect and group technology. Under slack due-date assignment, our objective is to determine the optimal sequence of jobs and groups, optimal due-date assignment, and optimal resource allocation such that the weighted sum of earliness and tardiness penalties, common flow allowances, and resource consumption cost is minimized. For three special cases, it is proved that the problem can be solved in polynomial time. To solve the general case of problem, the heuristic, tabu search, and branch-and-bound algorithms are proposed.